Phase change materials of fatty amine-modified silicate clays of nano layered structures. Issue 38 (28th April 2017) - Liao, Chien-Yi; Chiou, Jau-Yu; Lin, Jiang-Jen
Abstract : The ODA/MMT/paraffin was considered as PCM for absorbing and releasing heat according to the environmental temperature change. Abstract : Fatty-amine modified silicate clays of layered structure were prepared by conventional intercalation of n -octadecyl amine ( n -C18 H37 NH2, ODA) into sodium montmorillonite clay (Na + -MMT). Organically modified clays are considered as a new type of phase change materials (PCM). At one equivalent ratio of ODA-HCl over Na + -MMT by an ionic exchange reaction, the interlayer galleries of the silicates' layered structure were expanded from 12 Å to 28 Å as measured by X-ray diffraction (XRD) analysis. As a result, the organoclay (ODA/MMT) became hydrophobic and spacing was accessible for incorporating a second organic compound, n -octadecane. Physical absorption of n -octadecane in ODA/MMT allowed interlayer spacing and further expansion from 28 Å to 30 Å. Absorption efficiency, defined as the weight of n -octadecane over ODA/MMT, ranged from 5.3 to 9.1 fold depending on the amount of ODA intercalation. Since n -octadecane is a kind of paraffin wax, a phase change temperature of 25–29 °C was observed. The n -octadecane was characterized by thermal gravimetric analysis (TGA) to study absorption efficiency of ODA/MMT. During the heating process, the ODA/MMT/ n -octadecane powder remained in solid state without any liquid leakage at 80 °C (far beyond the phase change temperature). Thus, the organoclay (ODA/MMT) can be used as good thermal storage and phase change material.